Pelletization of fly ash for utilization in dynamic sorption processes - Vlahović Milica; Djordjević Nataša; Vušović Nenad; Vlahović Milan; Avramović Jelena; Veljković Nikola; Savić Aleksandar (Podzemni Radovi)
Fly ash, a byproduct of coal combustion in thermal power plants, has transitioned from industrial waste to a valuable technogenic raw material. Its alumino-silicate composition, porous structure, large specific surface area, and sorption activity make fly ash an efficient and low-cost sorbent for removing metal ions from acidic mine waters but only in discontinuous (static) systems. Its small particle size and poor hydraulic properties limit its application in continuous (dynamic) water treatment systems. This study aims to produce fly ash pellets with suitable properties for use as a sorbent in dynamiccolumn purification systems. By agglomerating fly ash with cement and plasticizer, pellets with enhanced mechanical properties such as compressive strength, impact strength, abrasion resistance, and disintegration time in water were developed. These pellets promise to improve the applicability and effectiveness of fly ash in dynamic water treatment processes, offering an economical and efficient solution for removing metal contaminants from wastewater.